Mangrove root crab Goniopsis cruentata (Latreille, 1803) processed meat quality by artisanal fisherwoman’s in Cajazeiras, Sergipe-Brazil (Research, Society and Development, 2023)
In Sergipe, the mangrove root crab (Goniopsis cruentata, Latreille), known in Brazil as “aratu” is considered one of the main fishing resources for the artisanal fisherwoman in Cajazeiras, Sergipe-Brazil, since mangrove root crab meat chain process is a culture and traditional work activity passed down for generations. So far, no studies assessed the quality of the processing performed by artisanal fishers in Cajazeiras. Therefore, this study aimed to investigate physico-chemical and microbiological characteristics of packaged or unpackaged meat in vacuum of these artisanal fisherwoman’s. The results revealed that the packaging process of the vacuum mangrove root crab meat did not favor the development of thermotolerant coliforms microorganisms, different from the results obtained in the mangrove root crab meat sample packed only in polyethylene bags. It was also found that samples of mangrove root crab meat packed in vacuum and in low density polyethylene bags showed no evidence of coagulase positive Staphylococcus, as well as the absence of Salmonella sp. It should be emphasized that the use of vacuum packaging may be a method that will increase the shelf life of the product, since the intrinsic factors of the sample such as alkaline pH and relatively high humidity are already positive factors for the development of microorganisms.